Individual differences from the perspective of islam and psychology - Nurfadilah Tanjung; Mufti Fatihatus Sakana; Ma’nusatul Khauro; Afriliani Zulaikha; Ibrahim bin Salem; Kana Safrina Rouzi (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
Education is essential for knowledge transfer and holistic individual development. A key factor in effective education is recognizing individual differences in physical, intellectual, and psychological aspects. Islam views human diversity as part of Allah’s will, emphasizing respect and cooperation, as highlighted in Surah Ar-Rum (30:22) and Surah Al-Hujurat (49:13). Islam also advocates for education tailored to individual capacities. Psychology reinforces this perspective, emphasizing the role of cognitive abilities, learning styles, and motivation in education. Theories like Gardner’s multiple intelligences and Tomlinson’s differentiated instruction highlight the need for personalized learning approaches. Using a qualitative library research method, this study finds that both Islamic and psychological perspectives support inclusive and adaptive education. Integrating these insights enables educators to design curricula that maximize each student's potential, fostering a knowledgeable and ethical generation